Investigation of NanoSQUIDs Fabricated with a Range of Focused Ion Beam Sources. (June 2020) - Polychroniou, E; Gallop, J; Godfrey, T; Cox, D; Long, G; Chen, J; Romans, E; Hao, L
Abstract: SQUIDs (Superconducting Quantum Interference Devices) are macroscopic quantum devices capable of detecting and measuring a wide variety of physical parameters with unprecedented sensitivity. SQUIDs based on nanobridge weak links have shown increasing promise for quantum information and quantum sensing applications such as single spin detection. Focussed ion beam etched nanobridges have properties which can enhance nanoSQUID device performance but are often limited in terms of their non-hysteretic operating temperature range. Here we describe measurements of FIB-milled nanobridges, as single weak links or in nanoSQUIDs, made using either Ga, Xe or Ne ion beam sources. Their properties as a function of temperature, bias current, magnetic field and microwave power are measured and modelled according to a range of superconductivity models, as a means for improved understanding of the associated nanobridge parameters. We further propose techniques to extend the non-hysteretic operating temperature range of the devices.